Sinonasal inverted papilloma; recurrence, malignant transformation and risk factors - Alexandru Meius; Teodora Ghindea; Catalina Pietrosanu; Irina Ionita; Daniel Timofte; Cornelia Nitipir; Laura Mazilu; Andreea Rusescu; Silviu Pituru; Razvan Hainarosie (Journal of Mind and Medical Sciences)
Sinonasal inverted papilloma is a rare benign epithelial tumor. Its three main clinical characteristics are the tendency of recurrence, the destructive ability of nearby structures and malignant transformation. The primary manifestations of this tumor include nasal obstruction, headaches, runny nose, hemorrhage and impaired sense of smell. The diagnosis is based on the clinical and endoscopic examination completed by CT or MRI scans and biopsy of the lesion. Allergies, chronic inflammation, nicotinism and viral infections such as HPV infection are considered possible causes of pathogenesis and potential risk factors for relapse and malignancy. The treatment for this condition is the complete removal of the tumor with disease-free margins. Postoperative follow-up is essential for the early detection of recurrence or malignant transformation. One of the most basic and important steps in managing these patients is to acknowledge the presence of the mentioned risk factors and avoid exposure. Due to the high risk of relapse, the follow-up must be aggressive and thorough and always include the endoscopic examination. In our article, we wish to highlight the importance of the proper surgical intervention, but also the difference in the overall outcome of the patient ensured by the correct management of the risk factors, allowing us to prevent recurrence and malignant transformation.